A novel method for spatially-resolved thermal conductivity measurement by super-resolution photo-activated infrared imaging. (May 2021) - Marini, Mario; Bouzin, Margaux; Sironi, Laura; D'Alfonso, Laura; Colombo, Roberto; Di Martino, Daniela; Gorini, Giuseppe; Collini, Maddalena; Chirico, Giuseppe
Abstract: Thermal conductivity measurements play a crucial role in most areas of the applied physical sciences, thereby constantly demanding for new non-invasive methods capable of providing high-resolution spatial mapping of absolute thermal conductivities on heterogeneous samples ranging from solid-state bulk materials to low-dimensionality structures. In this work, we lay the theoretical foundations and provide the experimental demonstration of a novel method for quantitative thermal conductivity mapping at tunable ∼10-μm resolution, by non-contact infrared photo-activated thermography. Starting from Fourier's heat transfer law, we surmise a universal dependence of the thermal response of a laser-irradiated sample on its thermal conductivity, irrespectively of density and specific heat capacity. We demonstrate such a dependence over the three conductivity decades 0.1–100 W/mK by finite-element numerical simulations, and exploit it for proof-of-principle single-point thermal conductivity measurements on both thermally thick and thermally thin reference solid samples. We exemplify the feasibility of space-resolved measurements on eighteenth-century tin organ pipe fragments, where the product of the thermal conductivity times the sample thickness, imaged at 40-μm sub-diffraction resolution, is pointed out as a relevant parameter for the non-destructive characterization of the sample conservation state. By coupling temperature maps with the extraction of thermal properties at high spatial resolution, our approach significantly expands the capability of state-of-the-art infrared imaging technology in fully capturing the compositional heterogeneity and/or functional state of the imaged materials. Graphical abstract: Image 1 Highlights: Photo-thermal imaging allows space-resolved thermal conductivity measurements. Thermal conductivity mapping at tunable ∼10-μm sub-diffraction resolution. Finite-element simulations are employed to derive a universal scaling law. Conductivity measurements on heterogeneous thermally thin and thick solid samples. Assessment of the sample deterioration and conservation state.